Factors affecting students' reluctance to work at university “A Field Study for Students of the Faculty of Arts at the Universities of Damascus and Tishreen”" - Barqawi, Hanaa; Esmael, Randa (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The importance of the university lies in the fact that it occupies a prominent place in the educational ladder, and that education in universities represents a high value and an effective means of promoting the different societies The study aims to: 1 - identify the factors leading to the reluctance of students of the Faculty of Arts in Damascus and about the youth university in the Faculty of Arts in Damascus from their point of view. 2- To identify demographic factors related to gender, school year and type of work for students of the Faculty of Arts in Damascus and Tishreen The main findings of the study: • There is favoritism for some of the students by Dr • The whole university and Astat and favoritism • The transportation crisis prevents me from reaching the university on time • The Dr.'s style is not encouraging and reads the article from the book • Dr. does not give me the mark that I deserve and feel injustice because of it